The Role of Dreams in Political-Religious Legitimacy in the Era of the First Islamic Caliphs - Razieh Afsharifar; Yaghoub Panahi (تاریخ اسلام و ایران)
The interpretation of dreams has always been of interest to societies, especially rulers, in various historical periods in order to predict events and providing information about the fate of people. Among Muslims, dreams and their interpretation are considered a divine science that can have a significant impact on the individual, social, and political life of societies. One of the periods in which Muslim rulers paid attention to dream narration and interpretation is the era of the Three Caliphs. By examining and analyzing the content of dreams narrated by the first caliphs of Islam, an attempt is made to show that these dreams were narrated by the apparatus of power with specific aims and motives. On this basis, the main question is how and with what themes the institution of power used dreams to legitimise the discourse of the caliphate, especially in the political and religious spheres. The dream was narrated by religious leaders, especially the Messenger of Allah, about caliphs or their relatives, with themes such as the resemblance of the new rulers of Islamic society to the Prophet, justification of their actions and their approval by the Prophet, gaining the support of the people, etc., with the aim of the justifying the political legitimacy of the caliphs and promoting their legitimacy. The central signifier of the dreams pursues political goals in an attempt to establish the legal status of the caliphs as the rightful successors of the prophet in the public. The method of this research is descriptive-analytical and uses a library method of data collection.